GREEN FINANCE, CASH FLOW, AND TAX AVOIDANCE: EVIDENCE FROM A DEVELOPING ECONOMY - Gretward Melky Tsay; Francis Hutabarat; Harlyn L Siagian (MESP–FEB UNS, 2026)
Green finance has emerged as a tool expected to increase transparency and reduce tax evasion, as the complexity of transactions in the banking sector creates significant opportunities for aggressive fiscal planning. However, there is still little concrete evidence demonstrating the relationship between the two. This study examines whether operational cash flow influences the relationship between green finance and tax avoidance in the Indonesian banking sector, where OJK Regulation No. 51/POJK.03/2017 mandates green finance but the consequences of its fiscal behavior are poorly understood. A group of 18 banks included in the Infobank15 Index was analyzed, resulting in 64 annual observations for the period 2021–2024. Green finance is measured as the proportion of environmentally oriented loans, operating cash flow is normalized by total assets, and the effective tax rate is used to indicate tax avoidance. Moderated regression analysis was performed using the Jamovi program. The results of the moderated regression analysis indicate that green financing does not have a significant direct effect on tax avoidance (β = 0.199, p = 0.330), while operational cash flow has a positive effect (β = 0.028, p = 0.001), with a negative interaction term (β = -0.094, p = 0.001). This indicates that operational cash flow moderates the relationship between green financing and tax avoidance. These results add to the literature on sustainable taxation, establish operational cash flow as an important boundary condition for green fiscal effects, and offer practical guidelines for regulators and bank management in building an environmentally friendly fiscal compliance framework.